Esoterismo e ocultismo em Fernando Pessoa: caminhos da crítica e de poética - Ribeiro, Rogério Mathias (2009)
This is a critical analysis of Fernando Pessoa s esoteric poetical production, according to his orthonym, whose interests relies on the esoteric teachings and on the secrets of occultism. This essay is about the influence of these subjects in the scope of his poetry, which, somehow, is considered a kind of occultist philosophy". Once more, we are going to study different researchers critical perspectives about this theme, such as António Telmo, António Quadros, Dalila Pereira da Costa and Yvette Kace Centeno, while trying to keep up with the inquiry on Fernando Pessoa s involvement with Masonry and other orders alike. This essay s target is to demonstrate the role and the relevance of the esoteric and occultists influences in the workmanship and the poetical project of Fernando Pessoa, as well as understanding the close relationship between poetry and alchemy regarding his poetical legacy. It s also a critical reading of this writer s esoteric poetry based on the mentioned aspects. In other words, this work consists of an analysis of Pessoa s poetical project as a alchemic way of producing the most sophisticated kind of poetry, as well as the effects of his relationship with all these esoteric elements. Therefore, we are going to study the mission of the poetry.